2009
DOI: 10.2174/1874613600903010031
|View full text |Cite
|
Sign up to set email alerts
|

New Options in the Treatment of Lipid Disorders in HIV-Infected Patients

Abstract: Since the introduction of HAART, there was a remarkably change in the natural history of HIV disease, leading to a notable extension of life expectancy, although prolonged metabolic imbalances could significantly act on the longterm prognosis and outcome of HIV-infected persons, and there is an increasing concern about the cardiovascular risk in this population. Current recommendations suggest that HIV-infected perons undergo evaluation and treatment on the basis of the Third National Cholesterol Education Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…Especially, the use of PIs is associated with an increased risk for lipid disorders. 6,25,26 This is in correspondence with our data. We found patients on PI-based ART to have higher FRS than patients on a non-PI-based ART.…”
Section: Discussionsupporting
confidence: 93%
“…Especially, the use of PIs is associated with an increased risk for lipid disorders. 6,25,26 This is in correspondence with our data. We found patients on PI-based ART to have higher FRS than patients on a non-PI-based ART.…”
Section: Discussionsupporting
confidence: 93%
“…The search for vaccines to protect against HIV/AID has continued to elude the science world. However, the use of highly active antiretroviral therapy (HAART) has dramatically improved the prognosis of HIV-infected individuals 1,2 .The beneficial effect of reduced risk of early death from opportunistic infections and other consequences of HIV infection, is however, reduced because other possible causes of death have replaced this beneficial effect 3 . Myocardial infarction has become a matter of particular concern.…”
Section: Introductionmentioning
confidence: 99%
“…study group reported an association between myocardial infarction and cumulative exposure to indinavir and lopinavir/ritonavir [ 5 ]. PI may increase total cholesterol and triglyceride levels and decrease HDL-cholesterol levels as a consequence of longer action of sterol regulatory element-binding protein-1 (SREBP-1) and protein kinase C activation [ 31 ]. However, the D.A.D.…”
Section: Discussionmentioning
confidence: 99%